Sum factorization of the static condensed Helmholtz equation in a three‐dimensional spectral element discretization. Issue 1 (December 2014) - Huismann, Immo; Haupt, Lars; Stiller, Jörg; Fröhlich, Jochen
Abstract We propose a factorization technique for the Helmholtz operator of a static condensed, three‐dimensional, cartesian spectral‐element discretization, that yields linear complexity in the number of degrees of freedom. We then compare its performance to a reference implementation of the conventional, unfactorized approach. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)